Identification of Costs Structure Change in Road Transport Companies - Milos Poliak; Juraj Hammer; Kelvin Cheu; Marek Jaskiewicz (Communications - Scientific letters of the University of Zilina, 2019)
The costs of each company on the market are an essential component of financial decision making, not only on the price of the goods and services provided, but also about the business efficiency. In business, services have a significant impact on pricing, but also for deciding on the realization of performances. Costs structure is composed of fixed and variable costs. Changing the costs structure creates assumptions for other decisions, as well as the pricing of the entrepreneur. The goal of this article was to identify, whether there is a change in time of the costs structure.